Assessment of Risk Communication Strategies and Community Engagement on Banditry and Kidnapping in Taraba State - Jimenda, Gideon D.; Ngantem, Linus M. (Darul Yasin Al Sys, 2025)
This study aims to examine the effectiveness of risk communication and community engagement as strategies to mitigate the pervasive issues of kidnapping and banditry in Nigeria. The study is grounded in Situational Crisis Communication Theory. A descriptive survey was employed as the research design to collect data from 400 respondents across five local government areas in southern Taraba. The study found that media anti-terrorism campaigns and the issuance of early warning signals to communities were the most effective risk communication and community engagement strategies used to mitigate the spate of kidnapping and banditry in southern Taraba. However, the effectiveness of the aforementioned strategies was limited by inadequate support from the government and poor media collaboration with other relevant stakeholders. Among other recommendations, the study suggests that mass media should engage community members more frequently in discussions about security matters alongside security experts in order to narrow the communication gap between the two groups. Additionally, security agencies need to fully recognize the media as partners in progress in curbing insecurity in Nigeria, as traditional military approaches have proven insufficient in combating insecurity.